Community composition and phyto-diversity assessment of ganda roba and ganda shabbo sites in Damota natural vegetation, eastern Ethiopia. Issue 10 (October 2022) - Hussein, Abdulbasit
Abstract: Anthropogenic activities like overexploitation of natural vegetation and plantation of exotic species in degraded areas are commonly occurring in the natural vegetation of Ethiopia. Natural forests conserve plant species and provide a number of ecosystem services to society. This study focuses on the tree species composition and regeneration possibility of Ganda Roba and Ganda Shabbo in Natural Vegetation of Damota, Eastern Ethiopia. The sample of tree species were collected from 40 plots of 20 m × 20 m, while seedlings and saplings were collected from 160 plots of 5 m × 5 m and 320 plots of 1 m × 1 m, respectively from elevations ranging from 2039-3023 m. There were 47 tree species identified, belonging to 32 genera and 21 families, with Fabacaea being the most prominent family with the most species. The mean species richness of adult trees was 39 ± 2.4, for saplings 38 ± 6.5, and for seedlings, it was 34.5 ± 5.3. The average seedling density was 21850 ± 1131.37 individuals ha −1, for saplings 17162.5 ± 972.27 individuals ha −1, and of mature trees 12450 ± 2050.61individuals ha −1 . The mean basal area for trees, saplings, and seedlings were 267.65 ± 30.78 m 2 ha −1, 68.6 ± 4.12 m 2 ha −1, and 45.83 ± 2.86 m 2 ha −1, respectively. Good regeneration was seen in 41% of total species in the Ganda Roba site while in Ganda Shabbo fair regeneration was seen in 44% of species. In Ganda Roba and Ganda Shabbo sites, 7% and 6% of species exhibited no regeneration respectively. Density-diameter distribution curve exhibited a consistent reduction in tree densities with an rise in DBH patterns. The current study provides baseline information for foresters and policymakers to better manage the forest for sustaining tree diversity and regeneration patterns and formulate better strategic conservation plans for the future. Abstract : Damota; Diversity; Regeneration; Structure; Tropical forests.